A review of complications of maxillary sinus augmentation and available treatment methods - Kim, Joongmin; Jang, Hyonseok (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2019)
Maxillary sinus grafting is a dependable procedure that has been in use for a long time. However, clinical complications often arise. To prevent complications of maxillary sinus grafting, it is necessary to know the contra-indications, both for general implantation and for maxillary bone grafting. In addition, presence of various complications requires careful consideration of treatment method; therefore, dentists should be familiar with the treatment protocols. Complications can be divided into postoperative, immediate postoperative, and delayed postoperative complications. Particularly for the outpatient, it is necessary to quickly distinguish between treatable cases and cases for which transfer is required. The purpose of this review is to discuss the contra-indications, complications, and treatment options for complications of maxillary sinus graft.